The cartulary of Bushmead Priory - Fowler, G. Herbert (George Herbert), 1861-1940; Godber, Joyce (Publications of the Bedfordshire Historical Record Society ;, 1945)
The cartulary of Bushmead Priory The documents in the cartulary deal with the Priory's property and privileges. They are transcribed in Latin and accompanied by brief summaries in English. There is an extract from the Valor Ecclesiasticus setting out the assessment of the Priory in 1535. A map shows the extent of Bushmead Priory's property in 1347. Field names are mentioned in the text. The volume begins with tributes In Memoriam to Samuel Howard Whitbread (the President) and George Herbert Fowler (the Secretary and General Editor).